Utilization of Content Base Image RetrievalTechnique Based Sketch for Facial Recognition - Muhammad Said Hasibuan; Handoyo Widi Nugroho; Suhendro Yusuf (Prosiding International conference on Information Technology and Business (ICITB), 2016)
As the rising up Including terrorist crimes in our society due to issues politics, economy, poverty, religion and ethnic conflicts. Many ways and techniques have been tried to crack down Reviews those crimes, but unfortunately the Efforts to seize person or group of suspected criminal is far from our expectation. Face recognition is one of techniques Introduced by many Researchers for the last Decades with many methods and approaches they tried to Recognize a person based on his or his faces. Some of the methods such as face recognition with Query by Example (QBE) using shape, color, and texture to match a query face with the face in the database; however the result is not good enough to Recognize the faces. One of the problems of face recognition by QBE is sometime we do not have a picture or a face image to the make QBE. In order to sort it out the problem, in this research we will try to introduce of face recognition method by generating a face image by a face sketch.Many sketch based face recognition was Introduced by some Researchers and experts, but most of reviews their methods have been applied directly inputting a sketch into a database the which is very costly and Involved a complex algorithm. In addition to the research, we are applying our proposed method compressed into face images, as the compressed images will save storage and unsumming the algorithm. KEY WORDS: Query by Example, Face recognition, criminal